KETERSEDIAAN DAN POTENSI SUMBER DAYA LAHAN UNTUK MENDUKUNG KETAHANAN PANGAN DI DESA PUTUN KECAMATAN NUNKOLO KABUPATEN TIMOR TENGAH SELATAN - Otu, Demi Alfonsus; Samin, Mikael; Pamungkas, Bella Theo Tomi (Universitas Nusa Cendana, 2024)
The increasing population in Putun Village must be accompanied by the availability of food supplies. The absence of research on food security in Putun Village is a problem in itself. This research aims to (1) determine the potential of land in Putun Village, Nunkolo District; (2) knowing food security in Putun Village, Nunkolo District. This research method is quantitative correlational inferential statistics. The sample used in this research was 202 families. Data collection techniques are questionnaire observation and documentation. Data analysis used in this research is hypothesis testing, questionnaire scoring with the Gutman scale and food expenditure share. The results of this research show that Putun Village is 5.15 km, located at an altitude of 0.1 meters above sea level with characteristic types of rocky and swampy soil. Land Use in Putun Village explains that land in Putun Village with an area of 2.8 km: is used for agriculture, land in Putun Village with an area of 1.6 km: is used for settlement, and land in Putun Village with an area of 0.75 km: no used or abandoned. Land potential in Putun Village with very good quality land for agriculture. However, there are several areas that have poor land quality because the land used is rocky land. And based on the results of the share of food expenditure (PPP) ≤60%, it can be said that households in Putun Village are food secure households, testing the hypothesis that there is an influence of land potential towards food security where the significance value (sig.) of 0.01 is smaller than the probability of 0.05 so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of land potential on food security.